Basis to implement an economic, financial and management consultancy services for the MSMEs - Pérez, Johemir
This article aims to make a compilation and analysis of relevant and up-to-date information that provides input to see the feasibility and implications of the start-up of a consultancy service for small and medium-sized enterprises rendered by Centro de Servicios Financieros (CSF); this article is derived from the research project "Implementation of consultancy for the economic, financial and management areas of MSMEs enterprises of Bogotá and Cundinamarca of CSF" financed by SENNOVA since 2016. This bibliographical review article seeks to contextualize interested readers about the nature of consultancies (particularly as regards economic issues) and previous experiences in Colombia, as a result, interesting practices that can be a replica model to be implemented within the CSF are identified to set up a portfolio of services for MSMEs that cannot afford specialized consultancy and need a great deal of support to guarantee their profitability and sustainability in the medium and long term.